2015
DOI: 10.1371/journal.pone.0145980
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Sea Turtle Density and Abundance in the Southeast Florida Current and Surrounding Waters

Abstract: Assessment and management of sea turtle populations is often limited by a lack of available data pertaining to at-sea distributions at appropriate spatial and temporal resolutions. Assessing the spatial and temporal distributions of marine turtles in an open system poses both observational and analytical challenges due to the turtles’ highly migratory nature. Surface counts of marine turtles in waters along the southern part of Florida’s east coast were made in and adjacent to the southeast portion of the Flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Seasonal variation in turtle density and abundance can also be studied using aerial surveys; however, these techniques are expensive and can be strongly affected by the presence of turtles on the sea surface during the surveys (Lauriano et al, 2011; Bovery & Wyneken, 2015). In Italy bycatch assessment often suffers of logistical problems in data collection, since the information is usually obtained from on board observations involving short periods of time, a limited number of vessels, and small area covered; moreover, sampling procedures are often not standardized (Dmitrieva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal variation in turtle density and abundance can also be studied using aerial surveys; however, these techniques are expensive and can be strongly affected by the presence of turtles on the sea surface during the surveys (Lauriano et al, 2011; Bovery & Wyneken, 2015). In Italy bycatch assessment often suffers of logistical problems in data collection, since the information is usually obtained from on board observations involving short periods of time, a limited number of vessels, and small area covered; moreover, sampling procedures are often not standardized (Dmitrieva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 10 years, satellite tracking has provided important information on many aspects of the biology, ethology, distribution and migration routes of C. caretta ( Hays et al, 1991 ; Hays, 1992 ; Godley et al, 2003 ; Zbinden et al, 2008 ; Casale et al, 2012 ; Luschi & Casale, 2014 ; Lucchetti et al, 2016 ) and bycatch estimates in the Mediterranean Sea have been reported for several countries and fishing gears. Seasonal variation in turtle density and abundance can also be studied using aerial surveys; however, these techniques are expensive and can be strongly affected by the presence of turtles on the sea surface during the surveys ( Lauriano et al, 2011 ; Bovery & Wyneken, 2015 ). In Italy bycatch assessment often suffers of logistical problems in data collection, since the information is usually obtained from on board observations involving short periods of time, a limited number of vessels, and small area covered; moreover, sampling procedures are often not standardized ( Dmitrieva et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several works have reported the effects of environmental [ 30 , 48 , 49 , 50 ] and anthropogenic disturbances [ 51 , 52 , 53 , 54 , 55 ] on turtle populations dynamics and distribution, migration corridors, species co-occurrence, the oxidative stress of nesting females, genetic structures, and connectivity between nesting and foraging areas and global threats for foraging habitats, namely threats for foraging habitats in the Gulf of Mexico. Chemical contamination is one of the biggest threats in the region for the turtles’ reproduction and nesting migratory movements, and is responsible for the degradation of foraging habitats and the occurrence of embryonic deformities [ 45 , 48 , 56 , 57 ]. Levels of contaminant exposure in marine turtles may vary according to the level of contamination and the time spent on foraging grounds [ 58 ], although the exact impact of chemical pollutants on sea turtles’ health is unknown and there is no information available on their toxicological effects or thresholds for any marine reptiles.…”
Section: Introductionmentioning
confidence: 99%
“…Dedicated aerial surveys are considered one of the most robust tools to gather information on sea turtle density, abundance and distribution [7,10,26], but while aerial line transect distance sampling surveys are regularly used worldwide to assess these population parameters for sea turtles [27][28][29][30][31][32], in the Mediterranean Sea, this approach has been used primarily to monitor Cetaceans [33][34][35][36][37][38]. Only recently aerial surveys have been used to assess loggerhead turtles' abundance at a regional level [39], with relatively little effort allocated in the past [35,40,41].…”
Section: Introductionmentioning
confidence: 99%